Applying the Brocher Declaration to short-term experiences in global health in dental education - Rosenbaum, Edward; Lasker, Judith; Prasad, Shailendra; Shick, Elizabeth (Frontiers in Education, 2023)
Participating in Short-Term Experiences in Global Health (STEGHs) has become an increasingly popular way for dental students to learn about the global burden of disease and health inequalities by traveling to a low-income community. However, there is little information available in the dental education literature providing guidelines on best practices for STEGHs. Often little is known about the local dental practice laws and ethics guidelines. One useful resource is the Brocher Declaration. The Brocher Declaration, created by the Advocacy for Global Health Partnerships (AGHP), is a comprehensive document outlining best practices for developing ethical and sustainable global health partnerships. The six guiding principles are: (1) mutual partnership with bidirectional input and learning, (2) empowered host country and community-defined needs and activities, (3) sustainable programs and capacity building, (4) compliance with applicable laws, ethical standards, and code of conduct, (5) humility, cultural sensitivity, and respect for all involved, and (6) accountability for actions. The principles of the Brocher declaration can serve as a foundation for ethics and sustainability and can be easily applied to STEGHs in dental education. The authors present a set of recommendations specific to each principle to guide dental schools in offering STEGHs to their students. Participating in STEGHs represents a unique opportunity for students to learn about the global burden of oral disease, its risk factors, and the population and public health strategies to reduce oral disease in diverse populations. When done ethically, they may serve as a spark for students to become future leaders in global health.